Problem-based learning to enhance students’ understanding and motivation for learning mechanics - Khalid, Madihah; Rahman, Hassan (Institute of Education, International Islamic University Malaysia, 2014)
This action research study sets out to investigate whether Problem-Based Learning (PBL) would enhance the technical students’ level of conceptual understanding and motivation for learning the subject of mechanics. This action research study involved a single classroom from a technical college where the instructional intervention was implemented for about 4 weeks (a total of 8 lessons). Quantitative data was generated through the administration of Pre and Post-tests, rubrics and questionnaires, while qualitative data was collected through lesson observations and interviews. Based on the results obtained, the sample students in general were found to make the desired improvement in their level of conceptual understanding of Mechanics. Comparison made based on a phase-test with a parallel group also showed that the sample students performed better than their immediate counterparts. With PBL, the students felt that focusing authentic engineering problems made the subject more relevant to their interests while the collaborative learning approach in the PBL setting made students share ideas and support each other thus enabled them to grasp the conceptual understanding required.